Impact of Financial Leverage on the Performance of Nepalese Commercial Banks - Dulal, Ambika Prasad; Katwal, Subash Kumar; Khan, Md. Samim (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2023)
The objective of this study is to investigate the impact of bank leverage on performance (profitability) of Nepalese commercial banks. Banks are highly leveraged institutions; so, it is an important task to measure the relation between banks’ degree of financial leverage and performance. The sample size of this quantitative research guided by positivist research philosophy was twenty commercial banks of Nepal. The study has sought to explore the relationship between independent variable (debt ratio, DR & debt equity ratio, DER) and the dependent variables (net interest margin, NIM, return on assets, ROA, & return on equity, ROE). Bank performance was measured by ROA, NIM and ROE. These variables are the indicators of bank profitability and DR and DER are the indicators of leverage. The econometric method was applied in the study to investigate the relationship of financial leverage with performance of commercial banks. The study period covered ten years from 2012/13 to 2020/21. The data were analysed using descriptive statistics, correlation, simple regression, and multiple regression. Financial leverage was proxied by debt ratio and debt to equity ratio. The bank performance was measured by net interest margin, return on assets and return on equity. The results showed nonlinear relation between bank leverage and performance. It indicates that the bank management should pay attention while employing the borrowed funds to expand their business and operations.